A method for synthesizing selenium disulfide

CN122977323APending Publication Date: 2026-10-27RPM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611053217.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但是该方法存在硫化氢利用率低、环境污染等问题

Benefits of technology

[0009]本申请提供的合成方法,通过加入的硫粉与硒粉的质量来精确控制二硫化硒中的硒硫元素比例;通过在一定压力的惰性静态环境下合成二硫化硒,有效抑制了硒、硫的挥发损失,可制备硒硫元素比例要求极为精确的二硫化硒,且制备的二硫化硒质地致密,组分均匀,基本不存在偏析情况,外观更佳;通过惰性气体氛围且高压环境下合成,制备的二硫化硒氧化程度低,且合成方法对环境友好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977323A_ABST
    Figure CN122977323A_ABST
Patent Text Reader

Abstract

The application provides a synthesis method of selenium disulfide, which comprises the following steps: uniformly mixing selenium powder and sulfur powder to obtain a mixture; loading the mixture into a mold and placing the mold into a pressure synthesis device; after the pressure synthesis device is replaced with an inert gas, continuously introducing the inert gas to adjust the pressure to 0.15-1.0 MPa, sealing the pressure synthesis device, and heating to 110-240 DEG C to perform a heat preservation reaction; and obtaining the reaction product after cooling and demolding, thereby obtaining the selenium disulfide. The synthesis method has the advantages of high yield, high purity of the obtained product, controllable element ratio, good uniformity of components, no segregation, simple process, no harmful emission, stable batch, low cost and easy amplification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of inorganic material preparation technology, specifically relating to a method for synthesizing selenium disulfide. Background Technology

[0002] Selenium disulfide is an orange-yellow to orange-red powder with a slight hydrogen sulfide odor and is almost insoluble in water or organic solvents. It possesses pharmacological effects such as inhibiting sebum secretion, suppressing Malassezia growth, and preventing epidermal hyperplasia. It is effective in treating dandruff and seborrheic dermatitis of the scalp, and is therefore often formulated into shampoos or pharmaceutical-grade washes.

[0003] There are two main types of existing methods for preparing selenium disulfide: wet synthesis and pyrometallurgical synthesis.

[0004] In wet synthesis, selenite is typically produced by reacting selenite with hydrogen sulfide. Hydrogen sulfide gas is introduced into a selenite solution to generate selenium disulfide, which is then filtered, dried, and crushed to obtain the final product, selenium disulfide. However, this method suffers from problems such as low hydrogen sulfide utilization and environmental pollution.

[0005] In pyrometallurgical synthesis, the traditional method involves adding selenium and sulfur in a specific ratio to a sealed quartz tube and synthesizing at high temperatures. However, this method requires a temperature of 10°C. -5 Sealing pipes under negative pressure (Pa) requires high standards for equipment and personnel; the extremely high vapor pressure of sulfur and selenium at high temperatures can easily cause pipe rupture, and the small amount of material loaded leads to a sharp increase in production costs.

[0006] In summary, existing technologies still suffer from problems such as complex processes, high equipment requirements, difficulty in balancing product purity and cost, sulfur volatilization loss, and inaccurate control of element ratios. Summary of the Invention

[0007] In view of this, this application provides a method for synthesizing selenium disulfide, which simplifies the process flow, reduces equipment requirements, solves the problem of sulfur volatilization loss, achieves precise ratio of selenium and sulfur elements, and produces selenium disulfide with dense texture, uniform composition and high purity.

[0008] To achieve the above objectives, this application adopts the following technical solution: A method for synthesizing selenium disulfide is provided, comprising: Selenium powder and sulfur powder are mixed evenly to obtain a mixture; The mixture is loaded into a mold and placed into a pressure synthesis device. The pressure synthesis device is purged with inert gas. After the pressure is adjusted to 0.15~1.0MPa by continuing to introduce inert gas, the pressure synthesis device is sealed and heated to 110~240℃ for heat preservation reaction. After cooling and demolding, the resulting reaction product yields selenium disulfide.

[0009] The synthesis method provided in this application precisely controls the ratio of selenium and sulfur elements in selenium disulfide by adjusting the mass of added sulfur powder and selenium powder. By synthesizing selenium disulfide under an inert static environment with a certain pressure, the volatilization loss of selenium and sulfur is effectively suppressed. This method can prepare selenium disulfide with extremely precise requirements for the ratio of selenium and sulfur elements. The prepared selenium disulfide has a dense texture, uniform composition, and virtually no segregation, resulting in a better appearance. Furthermore, the synthesis method, conducted under an inert gas atmosphere and high pressure, produces selenium disulfide with a low degree of oxidation and is environmentally friendly.

[0010] The provided synthesis method uses pressure synthesis equipment (such as a high-pressure synthesis furnace) to avoid the problem of quartz crucibles used in traditional methods being prone to breakage when being removed from the furnace, thus reducing material costs and improving product yield. Attached Figure Description

[0011] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0012] Figure 1 This is a schematic diagram of the preparation process of selenium disulfide.

[0013] Figure 2 The images show the XRD patterns of selenium disulfide prepared in Examples 1-4. Detailed Implementation

[0014] A typical embodiment of this application provides a method for synthesizing selenium disulfide, comprising: Selenium powder and sulfur powder are mixed evenly to obtain a mixture; The mixture is loaded into a mold and placed in a pressure synthesis device. After the pressure synthesis device is purged with inert gas, inert gas is continued to be introduced to adjust the pressure to 0.15~1.0MPa (e.g., 0.15MPa, 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa, 0.7MPa, 0.8MPa, 0.9MPa, 1MPa, etc.). The pressure synthesis device is then sealed, and the temperature is raised to 110~240℃ (e.g., 110℃, 120℃, 130℃, 150℃, 180℃, 200℃, 220℃, 240℃, etc.) for heat preservation reaction. After cooling and demolding, the resulting reaction product yields selenium disulfide.

[0015] The selenium disulfide synthesis method provided in this application can be completed in a single step, including mixing, molding, pressurizing and heating, and demolding. It eliminates the need for the multi-step reactions, filtration, washing, and selenium recovery steps required in wet synthesis, as well as the high-vacuum sealing operation of traditional pyrometallurgical methods. The process is simple, the equipment is durable, and the material capacity is large, making it easy to scale up production. This method utilizes a single pressurization protection synthesis under a high-pressure inert gas environment (0.15~1.0 MPa), effectively suppressing the volatilization loss of selenium and sulfur, avoiding the localized temperature unevenness that may be caused by continuous gas flow, ensuring a stable and uniform temperature field in the reaction system, and accurately converting the selenium-sulfur feed ratio into product stoichiometry. The product purity consistently reaches over 99%, eliminating the need for multiple purifications. This method is particularly suitable for the preparation of high-end products with extremely strict requirements on the selenium-sulfur element ratio. The selenium disulfide obtained by high-pressure synthesis is dense and homogeneous in composition, with virtually no segregation, resulting in a better product appearance. Simultaneously, the inert gas atmosphere eliminates oxidation side reactions, ensuring the product is free of oxide impurities. The pressurized inert atmosphere ensures stable and controllable reaction conditions, resulting in consistent batch-to-batch quality. This overcomes the stringent requirements of traditional wet synthesis methods regarding heating rates and dropping speeds, facilitating direct industrial production. Furthermore, compared to existing publicly available technologies using quartz tube pyrolysis, this method eliminates the risk of tube bursts and avoids the use of toxic or expensive reagents such as hydrogen sulfide, acetic acid, and hydrazine hydrate in wet synthesis. This method also produces no harmful gas emissions, yields high batch sizes, requires minimal consumable replacement, and has significantly lower production costs than existing high-purity selenium disulfide preparation methods. In summary, while maintaining high purity (meeting pharmaceutical / cosmetic grade requirements), this method achieves comprehensive advantages such as precise control of elemental ratios, uniform and dense product texture, no oxidation or pollution, stable temperature field, and easy scale-up. It effectively solves core problems in existing technologies, such as the difficulty in balancing purity and cost, sulfur and selenium volatilization losses, imprecise elemental ratio control, and stringent equipment requirements.

[0016] In some preferred embodiments, the purity of the sulfur powder is 99% or higher, and more preferably 99.9% or higher; the particle size of the sulfur powder is less than 200 μm, for example less than 150 μm, less than 100 μm, less than 50 μm, etc.

[0017] In some preferred embodiments, the purity of the selenium powder is 99% or higher, more preferably 99.9% or higher; the particle size of the selenium powder is less than 200 μm, for example less than 150 μm, less than 100 μm, less than 50 μm, etc.

[0018] Controlling the particle size of sulfur powder and selenium powder can effectively increase the contact surface area between the two phases, which is beneficial for a complete reaction. More importantly, for selenium powder (density 4.46 g / cm³), 3 ) and sulfur powder (density approximately 1.95 g / cm³) 3The problem of large density differences can be solved by limiting the particle size, which can reduce the segregation caused by density differences. This makes it less likely for selenium powder to settle to the bottom and sulfur powder to float to the top, resulting in more uniform mixing. This ensures that the ratio of selenium and sulfur elements in subsequent high-pressure synthesis is precisely controllable, the product composition is consistent, and the reaction rate and product quality are effectively improved.

[0019] In some preferred embodiments, the mixture contains 52-56 wt% selenium powder, such as 52 wt%, 53 wt%, 54 wt%, 55 wt%, 56 wt%, etc., and 44-48 wt% sulfur powder, such as 44 wt%, 45 wt%, 46 wt%, 47 wt%, 48 wt%, etc., with impurity content not exceeding 1 wt%. By precisely controlling the feed ratio of sulfur powder to selenium powder and the impurity content, high purity is ensured; combined with a high-pressure inert process, the volatilization of selenium and sulfur is greatly reduced, resulting in a precise and stable selenium-sulfur ratio that meets the needs of high-end applications.

[0020] In some preferred embodiments, the mixing is carried out in a homogenizer; the mixing time is 1-5 hours, preferably 1-2 hours; the homogenizer is a V-type homogenizer. Using a V-type homogenizer for a certain mixing time ensures that the selenium powder and sulfur powder are fully and uniformly dispersed, avoiding localized component segregation, ensuring batch-to-batch consistency, and laying the foundation for subsequent high-pressure synthesis to obtain dense selenium disulfide with precise elemental ratios.

[0021] In some preferred embodiments, the heat preservation reaction time is 1 to 16 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, etc.

[0022] In some embodiments, the heating rate is 1~40℃ / min, such as 1℃ / min, 2℃ / min, 3℃ / min, 5℃ / min, 8℃ / min, 10℃ / min, 15℃ / min, 20℃ / min, 25℃ / min, 30℃ / min, 35℃ / min, 40℃ / min, etc.

[0023] In some preferred embodiments, the cooling is natural cooling.

[0024] In some embodiments, the inert gas includes one or more of nitrogen, argon, and helium.

[0025] In some preferred embodiments, the mold is a semi-enclosed mold.

[0026] In some preferred embodiments, the yield of selenium disulfide is 98% or more, preferably 99% or more.

[0027] To facilitate understanding of this application, the following description will be more comprehensive and detailed in conjunction with the accompanying drawings and preferred embodiments, but the scope of protection of this application is not limited to the following specific embodiments.

[0028] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of this application.

[0029] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this application are available on the market or can be prepared by existing methods.

[0030] The preparation process flow diagram of this application is as follows: Figure 1 As shown, the process mainly includes mixing, loading into the furnace, synthesis, cooling and demolding.

[0031] Example 1 (1) Mixing: 5600g of selenium powder with a particle size of less than 200μm and a purity of more than 99% and 4400g of sulfur powder with a particle size of less than 200μm and a purity of more than 99% are put into a V-type homogenizer for thorough mixing. The mixing time is controlled at 2h to obtain a mixture. The total impurity content is tested to be 2360ppm, which meets the requirement of less than 1wt%.

[0032] (2) Synthesis: The mixture is loaded into a covered mold (semi-closed type), placed in a high-pressure synthesis furnace, and the furnace cover is closed. After gas replacement with inert nitrogen gas, the pressure is increased to 1.0 MPa by continuing to fill with inert nitrogen gas. The furnace body is sealed, the heating rate is controlled at 40℃ / min, and the synthesis is carried out at 240℃ for 16 hours.

[0033] (3) Demolding: After cooling to below 50℃, open the furnace lid, remove the material from the furnace chamber, and demold to obtain 9984g of selenium disulfide blocks, with a product yield of 99.84%. Samples of the obtained selenium disulfide blocks were analyzed, and X-ray diffraction was performed. Figure 1 As shown, the product phase is pure selenium disulfide. Se content was tested by sampling the upper, middle and lower regions of the product. The test results are shown in Table 1. The average selenium content was 56.02% by ICP-OES (inductively coupled plasma optical emission spectrometry), with good compositional uniformity, soluble selenium <1ppm, and total impurity content of 0.2368wt%, meeting the requirement of less than 1wt%.

[0034] Comparative Example 1 The only difference between this comparative example and Example 1 is that in step (2), after the nitrogen gas is replaced, nitrogen gas is no longer introduced to increase the pressure.

[0035] 9011g of selenium disulfide blocks were obtained, with a product yield of 90.11%. Product loss was significant. Se content was measured by sampling the upper, middle, and lower regions of the product. The results are shown in Table 1. The average selenium content was 62.15%, significantly deviating from the composition of selenium disulfide, and there was obvious segregation of components. The soluble selenium content was 352ppm, and the impurity content was 1.12wt%.

[0036] Comparative Example 2 The only difference between this comparative example and Example 1 is that in step (1), the particle sizes of the selenium powder and sulfur powder are different, and the particle sizes of the selenium powder and sulfur powder are both 800~1000μm.

[0037] Se content was tested by sampling the upper, middle and lower regions of the product. The test results are shown in Table 1. The average selenium content was 56.01%, and there was segregation of components. The soluble selenium content was 89 ppm and the impurity content was 0.35 wt%.

[0038] Example 2 (1) Mixing: 5500g of selenium powder with a particle size of less than 150μm and a purity of more than 99% and 4500g of sulfur powder with a particle size of less than 150μm and a purity of more than 99% are put into a V-type homogenizer for thorough mixing. The mixing time is controlled at 1.5h to obtain a mixture. The total impurity content is tested to be 2345ppm, which meets the requirement of less than 1wt%.

[0039] (2) Synthesis: The mixture is loaded into a covered mold (semi-closed type), placed in a high-pressure synthesis furnace, and the furnace cover is closed. After gas replacement with inert nitrogen gas, the pressure is increased to 0.5 MPa by continuing to fill with inert nitrogen gas. The furnace body is sealed, the heating rate is controlled at 20℃ / min, and the synthesis is carried out at 200℃ for 12 hours.

[0040] (3) Demolding: After cooling to below 50℃, open the furnace lid, remove the material from the furnace chamber, and demold to obtain 9990g of selenium disulfide blocks, with a product yield of 99.90%. Samples of the obtained selenium disulfide blocks were analyzed, and X-ray diffraction was performed. Figure 1 As shown, the product phase is pure selenium disulfide. Se content was tested by sampling the upper, middle and lower regions of the product. The test results are shown in Table 1. The average selenium content is 55.03%, the composition is uniform, the soluble selenium is <1ppm, and the total impurity content is 0.2354wt%, which meets the requirement of less than 1wt%.

[0041] Example 3 (1) Mixing: 5300g of selenium powder with a particle size of less than 100μm and a purity of more than 99% and 4700g of sulfur powder with a particle size of less than 100μm and a purity of more than 99% were put into a V-type homogenizer for thorough mixing. The mixing time was controlled at 1.0h to obtain a mixture. The total impurity content was tested to be 2351ppm, which met the requirement of less than 1wt%.

[0042] (2) Synthesis: The mixture is loaded into a covered mold (semi-closed type), placed in a high-pressure synthesis furnace, and the furnace cover is closed. After gas replacement with inert argon gas, the pressure is increased to 0.25 MPa, the furnace body is sealed, the heating rate is controlled at 10℃ / min, and the synthesis is carried out at 150℃ for 8 hours.

[0043] (3) Demolding: After cooling to below 50℃, open the furnace lid, remove the material from the furnace chamber, and demold to obtain 9992g of selenium disulfide blocks, with a product yield of 99.92%. Samples of the obtained selenium disulfide blocks were analyzed, and X-ray diffraction was performed. Figure 1 As shown, the product phase is pure selenium disulfide. Samples were taken from the upper, middle and lower regions of the product to test the Se content. The test results are shown in Table 1. The average selenium content is 53.01%, the composition is uniform, the soluble selenium is <1ppm, and the total impurities are 0.2377wt%, which meets the requirement of less than 1wt%.

[0044] Example 4 (1) Mixing: 5200g of selenium powder with a particle size of less than 50μm and a purity of more than 99% and 4800g of sulfur powder with a particle size of less than 50μm and a purity of more than 99% are put into a V-type homogenizer for thorough mixing. The mixing time is controlled at 0.5h to obtain a mixture. The total impurity content is tested to be 2322ppm, which meets the requirement of less than 1wt%.

[0045] (2) Synthesis: The mixture is loaded into a covered mold (semi-closed type), placed in a high-pressure synthesis furnace, and the furnace cover is closed. After gas replacement with inert argon gas, the pressure is increased to 0.15 MPa by continuing to fill with inert argon gas. The furnace body is sealed, the heating rate is controlled at 1℃ / min, and the synthesis is carried out at 110℃ for 4 hours.

[0046] (3) Demolding: After cooling to below 50℃, open the furnace lid, remove the material from the furnace chamber, and demold to obtain 9994g of selenium disulfide blocks, with a product yield of 99.94%. Samples of the obtained selenium disulfide blocks were analyzed, and X-ray diffraction was performed. Figure 1As shown, the product phase is pure selenium disulfide. Se content was tested by sampling the upper, middle and lower regions of the product. The test results are shown in Table 1. The average selenium content is 52.01%, the composition is uniform, the soluble selenium is <1ppm, and the total impurity content is 0.2394wt%, which meets the requirement of less than 1wt%.

[0047] Comparative Example 3 The only difference between this comparative example and Example 4 is that in step (2), after the argon gas is replaced, the inert argon gas is continued to be introduced to increase the pressure to 0.15 MPa, keeping the inlet and outlet open, and nitrogen is continuously introduced during the subsequent reaction process to maintain the furnace pressure at 0.15 MPa.

[0048] Se content was tested by sampling the upper, middle and lower regions of the product. The test results are shown in Table 1. The average selenium content was 76.14%, which is seriously deviated from the composition ratio of selenium disulfide. There was also obvious segregation of components. The soluble selenium content was 7808 ppm and the impurity content was 3.67 wt%.

[0049] Comparative Example 4 The only difference between this comparative example and Example 4 is that in step (2), after the gas is replaced by inert argon gas, the pressure is increased to 0.12 MPa by continuing to fill with inert argon gas, the furnace body is sealed, the heating rate is controlled at 1℃ / min, the synthesis is carried out at 110℃, and the holding time is 4h.

[0050] Se content was tested by sampling the upper, middle and lower regions of the product. The test results are shown in Table 1. The average selenium content was 51.44%, which slightly deviated from the composition ratio of selenium disulfide. There was also a certain amount of segregation of components. The soluble selenium content was 448 ppm and the impurity content was 0.3877 wt%.

[0051] Example 5 The only difference between this embodiment and embodiment 4 is that in step (1), the mixing time is controlled at 0.2h.

[0052] Se content was tested by sampling the upper, middle and lower regions of the product. The test results are shown in Table 1. The average selenium content was 51.85%, the composition deviated from the selenium disulfide composition ratio, the composition showed segregation, the soluble selenium content was 476 ppm, and the total impurity content was 0.84 wt%.

[0053] Depend on Figure 2It can be seen that the curves of the samples obtained in Examples 1-4 basically overlap, the peak positions are basically the same, and no other impurity peaks appear, indicating that the reaction is complete and the product phase is pure selenium disulfide. At the same time, the analysis of the selenium content and soluble selenium content in selenium disulfide also indicates that the reaction is relatively thorough, and the synthesized product is pure selenium disulfide, which meets the product requirements.

[0054] Table 1 As shown in Table 1, the synthesis yields of Examples 1-5 are high and the impurity content of the products meets the requirements. Among them, the average Se content of the products obtained in Examples 1-4 meets the requirements, and the composition is uniform and there is no segregation.

[0055] As shown in Table 1, comparing Example 1 and Comparative Example 1, high-pressure synthesis can significantly improve product yield and accurately control the composition ratio of selenium disulfide, thus significantly improving composition uniformity. Comparing Example 1 and Comparative Example 2, by controlling the particle size of sulfur powder and selenium powder, the composition ratio of selenium disulfide can be accurately controlled, significantly reducing component segregation and improving product composition uniformity. Comparing Example 1 and Comparative Example 4, when selenium disulfide is synthesized under pressure, when the pressure is below 0.15 MPa (e.g., 0.12 MPa), the impurity content increases to a certain extent, and the free selenium content increases significantly, resulting in component segregation.

[0056] As shown in Table 1, comparing Example 4 and Comparative Example 3, it can be seen that compared to maintaining high pressure by continuously introducing nitrogen during the reaction process, achieving high pressure by introducing nitrogen in one go can not only significantly improve the product yield, but also accurately control the composition ratio of selenium disulfide, significantly reduce component segregation, and improve the uniformity of product components. Comparing Example 4 and Example 5, it can be seen that the mixing time has a certain impact on the uniformity of product components.

[0057] The above description is only a preferred embodiment of this application. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of this application, and these improvements and modifications should also be considered within the scope of protection of this application.

Claims

1. A method for synthesizing selenium disulfide, characterized in that, include: Selenium powder and sulfur powder are mixed evenly to obtain a mixture; The mixture is loaded into a mold and placed in a pressure synthesis device. The pressure synthesis device is purged with inert gas. After the pressure is adjusted to 0.15~1.0MPa by continuing to introduce inert gas, the pressure synthesis device is sealed and heated to 110~240℃ for heat preservation reaction. After cooling and demolding, the resulting reaction product yields selenium disulfide.

2. The method for synthesizing selenium disulfide as described in claim 1, characterized in that, The sulfur powder has a purity of 99% or higher and a particle size of less than 200 μm.

3. The method for synthesizing selenium disulfide as described in claim 1, characterized in that, The purity of the selenium powder is above 99%; the particle size of the selenium powder is less than 200 μm.

4. The method for synthesizing selenium disulfide as described in claim 1, characterized in that, The mixture contains 52-56 wt% selenium powder, 44-48 wt% sulfur powder, and no more than 1 wt% impurities.

5. The method for synthesizing selenium disulfide as described in claim 1, characterized in that, The mixing is carried out in a homogenizer; the mixing time is 1 to 5 hours, preferably 1 to 2 hours; the homogenizer is a V-type homogenizer.

6. The method for synthesizing selenium disulfide as described in claim 1, characterized in that, The heat preservation reaction time is 1~16h.

7. The method for synthesizing selenium disulfide as described in claim 1, characterized in that, The heating rate is 1~40℃ / min.

8. The method for synthesizing selenium disulfide as described in claim 1, characterized in that, The cooling is natural cooling; The inert gas includes one or more of nitrogen, argon, and helium.

9. The method for synthesizing selenium disulfide as described in claim 1, characterized in that, The mold is a semi-enclosed mold.

10. The method for synthesizing selenium disulfide as described in claim 1, characterized in that, The yield of selenium disulfide is 98% or higher, preferably 99% or higher.